A bionic nanofiber aerogel with integrated thermal insulation, noise reduction and fire prevention functions and a preparation method thereof

Through directional freezing and freeze-drying processes, combined with high-temperature sintering, nanofiber aerogels with honeycomb pore structure are formed, which solves the problems of uneven structure and insufficient performance of traditional fiber aerogels, and achieves efficient and economical preparation and excellent performance.

CN118702483BActive Publication Date: 2025-02-28NAVAL UNIV OF ENG PLA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410965022.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-02-28
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

Traditional fiber aerogels are prone to settle during freeze-drying, resulting in uneven material structure. The existing nanofiber aerogels have poor compression and resilience performance in extreme environments, and the preparation process is complex and costly.

Method used

By utilizing the gel curing characteristics of hydrophilic colloids, the fiber matrix and infrared light shielding enhancement phases are quickly cured during the directional freezing process. Combined with freeze-drying and high-temperature sintering processes, ice crystals and hydrophilic colloids are removed to form a nanofiber aerogel with honeycomb pore structure.

Benefits of technology

The uniform structure of the fiber aerogel is achieved, and its compression rebound performance is improved in high and low temperature extreme environments, simplifies the preparation process, reduces costs, and enhances the heat insulation and sound absorption performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention discloses a bionic thermal insulation, noise reduction and fireproofing integrated nanofiber aerogel and a preparation method thereof, and belongs to the technical field of fiber aerogel. The preparation method of the bionic thermal insulation, noise reduction and fireproofing integrated nanofiber aerogel of the present invention comprises the following steps: mixing silica sol and water to obtain a premixed liquid, then adding a hydrophilic colloid and SiO2 nanofibers, mixing evenly, and obtaining a suspension; performing directional freezing on the suspension, and then vacuum drying and sintering to obtain the bionic thermal insulation, noise reduction and fireproofing integrated nanofiber aerogel. The present invention utilizes the property that hydrophilic colloids can gel with the change of temperature, and can quickly solidify to form a high-strength gel during the directional freezing process to solidify the fiber matrix and the infrared sunscreen reinforcing phase, and then removes ice crystals and hydrophilic colloids through freeze drying and high-temperature sintering, thereby solving the sedimentation problem of high-density reactants during the freezing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiber aerogels, and in particular to a bionic nanofiber aerogel with integrated thermal insulation, noise reduction and fire prevention functions and a preparation method thereof. Background Art

[0002] Traditional aerogels are prepared by the sol-gel method. The microstructure is a pearl-series skeleton structure composed of nanoparticles. However, the neck-type connection causes the mechanical properties of the aerogel to be poor, and it is easy to fall apart, which is not conducive to practical applications. Fiber aerogels use one-dimensional fibers as the basic component unit. By changing the neck-type connection to a fiber overlap connection, the mechanical properties of the aerogel are improved, which is more conducive to practical applications. With its good low density, low thermal conductivity, and compression rebound characteristics, it has broad application prospects in the fields of thermal insulation, air purification, seawater desalination, catalysis, and electromagnetic wave absorption.

[0003] Aerogels prepared by the traditional sol-gel method can obtain aerogels with uniform structure because the hydrolysis and polycondensation processes are carried out in situ and their basic components are microscopic particles with nanometer size. However, fiber aerogels are generally obtained by freeze-drying, and their basic components are macroscopic fibers with high density, which are very easy to settle during the freezing process, resulting in uneven structure of the final aerogel material. The structure of the lower layer is often denser than that of the upper layer, which affects its performance and practical application.

[0004] Traditional oxide fibers have strong permeability to infrared thermal radiation with a wavelength of 3 to 8 μm. In order to improve its high-temperature thermal insulation performance, researchers often add infrared sunscreens to reduce its infrared transmittance. Common infrared sunscreens include SiC, TiO2, B4C, etc. These infrared sunscreens need to be evenly distributed in the aerogel to give it good high-temperature thermal insulation performance. Therefore, it is necessary to improve the preparation process to make the infrared sunscreen evenly dispersed. The current preparation process of nanofiber aerogels often uses simple room temperature binders and thickeners, and cannot guarantee uniform distribution for fiber matrices and reinforcing phases (such as infrared sunscreens, etc.) with different densities. At the same time, current nanofiber aerogels often only focus on thermal insulation performance, and relatively little research on acoustic performance and fire resistance.

[0005] Patent CN110078425A adopts acrylamide system gel injection molding method, by making silica sol and acrylamide system gel injection molding premix with dispersed mullite nanofibers into gel, and finally obtains lightweight and heat-insulating mullite nanofiber aerogel through freeze drying and high-temperature calcination. However, the aerogel has poor compression resilience, and the acrylamide system used requires monomers, initiators, catalysts, etc. The gelation steps are cumbersome and the cost is high. It only focuses on thermal insulation performance and has a single application scenario.

[0006] Patent CN115304819A mixed silica nanofibers with soft skeleton materials and crosslinking agents, and successfully prepared hydrophobic elastic silica nanofiber aerogels by freeze drying. However, the raw materials used have high infrared transmittance and are not resistant to high temperatures, and cannot cope with extreme high temperature conditions. At the same time, the samples do not have anisotropic mechanical properties. Although they have certain elasticity, the compression rebound rate is low under large deformation conditions, and they cannot cope with extreme stress conditions during actual use. Summary of the invention

[0007] The purpose of the present invention is to provide a bionic nanofiber aerogel with integrated insulation, noise reduction and fireproof functions and a preparation method thereof to solve the above-mentioned problems in the background technology. The present invention utilizes the property that hydrophilic colloid can gel with the change of temperature, and can quickly solidify to form a high-strength gel in the directional freezing process to solidify the fiber matrix and the infrared sunscreen agent reinforcement phase, and then removes ice crystals and hydrophilic colloids through freeze drying and high-temperature sintering, solving the sedimentation problem of high-density reactants during the freezing process.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] One of the technical solutions of the present invention is to provide a method for preparing a bionic nanofiber aerogel with integrated thermal insulation, noise reduction and fire prevention functions, comprising the following steps:

[0010] The silica sol and water are mixed to obtain a premixed solution, and then a hydrophilic colloid and SiO2 nanofibers are added and mixed evenly to obtain a suspension;

[0011] The suspension is subjected to directionally freezing, vacuum drying and sintering to obtain the bionic nanofiber aerogel with integrated heat insulation, noise reduction and fireproof functions.

[0012] Preferably, the method for adding the hydrophilic colloid and SiO2 nanofibers is: after heating the premix to the dissolution temperature of the hydrophilic colloid, add the hydrophilic colloid, and after the hydrophilic colloid is completely dissolved, add the SiO2 nanofibers, continue stirring for 30 minutes, and obtain the suspension.

[0013] The suspension prepared by the present invention has no obvious precipitation and can maintain suspension stability for more than 30 minutes.

[0014] Preferably, the process of mixing the silica sol and water further includes a step of adding an infrared sunscreen; the mass ratio of the silica sol, infrared sunscreen, water, hydrophilic colloid and SiO2 nanofibers is 1-4:0-0.2:16-19:0.2:0.2.

[0015] Preferably, the silica sol, infrared sunscreen and water are mixed by ultrasonic dispersion in an ultrasonic cell disruptor for 5 to 20 minutes.

[0016] Preferably, the concentration of silicon dioxide in the silica sol is 10 wt %; and the hydrophilic colloid is one or more of agarose, pectin, gelatin, carrageenan, gellan gum and konjac gum.

[0017] Preferably, the infrared sunscreen is one or more of SiC whiskers, TiO2 particles, potassium hexatitanate whiskers and B4C particles; the diameter of the SiC whiskers and potassium hexatitanate whiskers is ≤1 μm, and the aspect ratio is ≤20; the particle size of the TiO2 particles and B4C particles is ≤1 μm.

[0018] Preferably, the preparation method of the SiO2 nanofiber is:

[0019] First, the SiO2 nanofiber membrane is cut into small pieces, and pre-cut using a wall breaking machine for 3 minutes to obtain a SiO2 nanofiber suspension without obvious SiO2 nanofiber membrane pieces, and then homogenized and cut at a speed of 3000-20000r / min for 5-20min to obtain a homogenous liquid, which is then dried at 120°C for 24h to obtain the SiO2 nanofibers.

[0020] Preferably, the directional freezing is as follows: the suspension is placed in a mold, and then the mold is placed in a directional freezing device with a unidirectional temperature gradient distribution for directional freezing; the bottom of the mold is in contact with a copper block in the directional freezing device with a unidirectional temperature gradient distribution, and the copper block plays a role of unidirectional freezing, the temperature of the copper block is -70°C to -196°C, and the time of the directional freezing is 30 to 120 minutes.

[0021] Preferably, the mold is a polytetrafluoroethylene mold; during the directional freezing process, the directional freezing device is surrounded by heat insulating cotton to isolate heat and ensure the unidirectionality of temperature transfer to the greatest extent.

[0022] Preferably, the internal ambient temperature of the dryer during vacuum drying is -50°C to 50°C, the water-filled cold trap temperature is -70°C to -45°C, the time is 72h, and the vacuum degree is 5 to 30Pa; the sintering is performed by heating the temperature to 800°C at a heating rate of 2°C / min and then keeping the temperature for 120min, and the sintering atmosphere is an air atmosphere.

[0023] The second technical solution of the present invention is to provide a bionic nanofiber aerogel with integrated insulation, noise reduction and fire prevention functions obtained according to the above preparation method.

[0024] Preferably, the density of the composite aerogel is 5 to 50 mg / cm 3The thermal conductivity at room temperature is 0.0208~0.0274W / (m·K), and the high temperature thermal conductivity at 800℃ is 0.0633~0.0787W / (m·K).

[0025] The technical principles of the present invention are as follows:

[0026] The present invention is inspired by the structure of white blind shrimps that survive in high-temperature volcanic crater waters. The filamentous bristle structure grown on the surface of its organs effectively improves the interfacial thermal resistance, giving the white blind shrimps good high-temperature heat resistance, and can withstand the high temperature of 450°C volcanic hot springs for a long time. At the same time, the non-filamentous bristle structure on its surface also increases the roughness of the wall, which is expected to increase the dissipation of sound waves. Therefore, the present invention designs a nanofiber aerogel with a honeycomb pore structure through the gel curing characteristics of hydrophilic colloids and the directional freeze-drying process. The pore wall has a large number of flexible fiber extension structures, which enhances the interfacial thermal resistance; the pore wall has a random distribution of infrared sunscreen agents, which can enhance the roughness of the wall; at the same time, the fiber matrix and infrared sunscreen agents bring high temperature resistance to the product, which can meet the requirements of fire prevention. The prepared nanofiber aerogel meets the characteristics of thermal insulation, noise reduction and fire prevention integration, and can be used in a wide range of practical applications.

[0027] The beneficial technical effects of the present invention are as follows:

[0028] The present invention utilizes directional freezing to construct a nanofiber aerogel with a honeycomb pore structure, which has an anisotropic structure, and its fiber matrix is ​​a flexible SiO2 nanofiber, which gives the aerogel excellent compression resilience performance, and under extreme environments of high and low temperatures, the aerogel can still maintain stable compression resilience performance, which can play a good buffering effect on the strong impact that may be encountered during the actual application process, and has good long-term usability. In the process of directional freeze drying, the shrinkage of the material is prevented to the maximum extent by the solvent sublimation method, and the cumbersome processes such as solvent replacement of the supercritical drying method are avoided, the preparation cycle is short, and it is easy to mass produce. Directional freezing can form a honeycomb pore structure, so that the infrared sunscreen agent is evenly distributed on the hole wall surface, and the dissipation effect on sound waves is enhanced.

[0029] The present invention utilizes the property that hydrophilic colloids in the food industry can gel with changes in temperature. During the directional freezing process, they can quickly solidify to form a high-strength gel to solidify the fiber matrix and the infrared sunscreen agent reinforcement phase, thereby solving the sedimentation problem of high-density reactants during the freezing process and ensuring the uniformity of the prepared product. The elastic gel network is squeezed through the directional growth of ice crystals to form a honeycomb pore structure, and then the ice crystals and hydrophilic colloids are removed by freeze drying and high-temperature sintering to form a multi-level maze bionic structure with fibers distributed in the holes and infrared sunscreen agents distributed on the hole walls. The present invention can allow high-density reactants to uniformly solidify and form gels in a short time through simple temperature control, breaking the inherent disadvantage that high-density additives are very easy to settle during the preparation process.

[0030] The density of the bionic thermal insulation, noise reduction and fire prevention integrated nanofiber aerogel prepared by the present invention is 5-50 mg / cm 3 The thermal conductivity at room temperature is 0.0208-0.0274 W / (m·K), the thermal conductivity at high temperature of 800°C is 0.0633-0.0787 W / (m·K), and the peak value of the sound absorption coefficient can reach 0.99. This product has superelasticity within the working temperature range, excellent thermal insulation performance under extreme conditions, and good sound absorption characteristics. The reaction controllability of the invention is strong, the preparation method is simple and environmentally friendly, and the cost is low. It has a wide range of applications and can meet the practical application of coating devices such as pipelines, valves, and high-temperature components. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 This is the axial microscopic morphology of the product of Example 1.

[0033] Figure 2 This is a radial microscopic morphology image of the product of Example 1.

[0034] Figure 3 This is a macroscopic morphology of the suspension in Example 2.

[0035] Figure 4 This is a macroscopic morphology of the product of Example 2.

[0036] Figure 5 This is a macroscopic morphology of the nanofiber aerogel prepared according to the method of Effect Example 1.

[0037] Figure 6The figure is a high temperature resistance effect diagram of the product of Example 3 under an alcohol lamp.

[0038] Figure 7 This is a diagram showing the high temperature resistance of the product of Example 3 under a butane blowtorch.

[0039] Figure 8 This is the compression-rebound diagram of the product of Example 4 at room temperature.

[0040] Fig. 9 This is a diagram showing the pressure-bearing effect of the product of comparative example 5 when placed above the pistil in a natural environment.

[0041] Fig.10 These are the actual pictures of the in-situ compression rebound of the product of Comparative Example 6 at -196°C and 600°C respectively.

[0042] Fig.11 The figure is a comparison chart of the compression-rebound curves of the products of Example 1 and Comparative Examples 1-3 at 60%.

[0043] Fig.12 It is a comparison chart of the compression-rebound curves of the product of Example 1 at 20%, 40%, and 60%.

[0044] Fig.13 It is a comparison chart of the compression-rebound curves of the products of Comparative Examples 4-8 at 60%.

[0045] Fig.14 This is a temperature difference diagram of the hot and cold surfaces of the product of Comparative Example 8 under a butane spray gun.

[0046] Fig.15 This is a comparison chart of the sound absorption coefficient of the product of Comparative Example 8 when cut to a thickness of 30 mm and that of commercial glass fiber felt.

[0047] Fig.16 The figure is a direct comparison of the thermal insulation and sound absorption performance of the product of comparative example 8 and other common materials. Among them, (a) is a physical picture of nanofiber aerogel, glass fiber felt, ceramic fiber felt, and carbon felt, (b)-(d) are temperature imaging pictures of each material after heating for 30s, 300s, and 600s, respectively, (e) is a physical picture of the device for measuring the sound absorption coefficient in a small reverberation chamber made by the present invention, and (f)-(h) are sound intensity cloud pictures when no sound absorbing material is placed, glass fiber felt is placed, and nanofiber aerogel is placed, respectively.

[0048] Fig.17The morphology comparison diagram of the product of Example 1 of the present invention and the filamentous bristle structure on the surface of the organ of the white blind shrimp. Among them, (a) is a macroscopic morphology diagram of the white blind shrimp, (b) and (c) are respectively microscopic morphology diagrams of the filamentous bristle structure on the surface of the organ of the white blind shrimp at different magnifications, (d) is an axial microscopic morphology diagram of the product of Example 1, and (e)-(f) are respectively radial microscopic morphology diagrams of the product of Example 1 at different magnifications. DETAILED DESCRIPTION

[0049] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0050] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0051] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the invention.

[0052] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0053] The "normal temperature" in the present invention is 20-30°C unless otherwise specified.

[0054] The preparation method of SiO2 nanofibers used in the following embodiments and comparative examples of the present invention is as follows: first, the SiO2 nanofiber membrane is cut into 1×1 cm 2 The small pieces were pre-cut by a wall breaking machine for 3 minutes to obtain a SiO2 nanofiber suspension without obvious SiO2 nanofiber membrane pieces, and then transferred to an IKAT25 high-speed homogenizer for homogenization and cutting at a speed of 13000r / min for 20 minutes to obtain a homogenous liquid, and then transferred to a 120°C oven for drying for 24 hours to obtain the SiO2 nanofibers.

[0055] The diameter of the SiC whiskers used in the following embodiments and comparative examples of the present invention is ≤1 μm, and the aspect ratio is ≤20; the diameter of the potassium hexatitanate whiskers used is ≤1 μm, and the aspect ratio is ≤20; the particle size of the TiO2 particles used is ≤1 μm; and the particle size of the B4C particles used is ≤1 μm.

[0056] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0057] Example 1

[0058] Preparation of nanofiber aerogel:

[0059] In a 150mL beaker, 72g of deionized water, 8g of silica sol (silicon dioxide concentration is 10wt%), and 0.4g of SiC whisker are added, and placed in an ultrasonic cell disruptor. Ultrasonic dispersion is performed at a power of 240W for 5min to obtain a uniform SiC whisker / silica sol premix, which is placed in a water bath at room temperature, and the stirring rate is adjusted to 600r / min. The water bath is gradually heated to 95°C. When the temperature of the premix reaches 95°C, 0.8g of agarose powder is added, and the stirring rate is adjusted to 1200r / min until the agarose powder is completely dissolved in the premix. Subsequently, 0.8g of SiO2 nanofibers is added, the stirring rate is adjusted to 1800r / min, and the stirring time is 30min to obtain a uniform suspension.

[0060] The suspension is placed in a polytetrafluoroethylene mold, and then the mold is placed in a directional freezing device with a unidirectional temperature gradient distribution. The bottom of the mold is in contact with the copper block in the directional freezing device, and the copper block plays a role of unidirectional freezing; the directional freezing is carried out for 90 minutes when the temperature of the copper block is -80°C. During the directional freezing process, the directional freezing device is surrounded by heat insulation cotton to isolate heat and ensure the unidirectionality of temperature transfer to the greatest extent.

[0061] After being completely frozen, it was transferred to a freeze dryer and vacuum dried for 72 hours at a vacuum degree of 16.6Pa and a water-filled cold trap temperature of -60°C. It was then transferred to a muffle furnace and heated to 800°C at a heating rate of 2°C / min in an air atmosphere, and kept warm for 120 minutes to obtain nanofiber aerogel (denoted as SWSNA1.0).

[0062] It was measured that the density of the product of Example 1 was 33.4 mg / cm 3 The compressive strength is 11.78KPa, the thermal conductivity is 0.0243W / (m·K) at room temperature, and the thermal conductivity is 0.0657W / (m·K) at 800°C. The product was cut into 50mm thickness, and its sound absorption coefficient at 800Hz was measured to be 0.94.

[0063] Figure 1This is the axial microscopic morphology of the product of Example 1.

[0064] Figure 2 This is a radial microscopic morphology image of the product of Example 1.

[0065] Depend on Figure 1-2 It can be seen that its axial direction is a typical honeycomb hole structure, and there are a large number of SiO2 nanofibers protruding inside the honeycomb holes. Infrared sunshades are attached to the radial honeycomb hole walls, which increases the roughness of the wall. This blind shrimp-like structure improves the thermal insulation and sound absorption properties of the material.

[0066] Example 2

[0067] Preparation of nanofiber aerogel:

[0068] In a 1000mL beaker, 540g of deionized water, 60g of silica sol (silicon dioxide concentration is 10wt%), and 6g of SiC whiskers are added, and placed in an ultrasonic cell disruptor. Ultrasonic dispersion is performed at a power of 960W for 10min to obtain a uniform SiC whisker / silica sol premix, which is placed in a water bath at room temperature, and the stirring rate is adjusted to 1000r / min. The water bath is gradually heated to 95°C. When the temperature of the premix reaches 95°C, 6g of agarose powder is added, and the stirring rate is adjusted to 1600r / min until the agarose powder is completely dissolved in the premix. Subsequently, 6g of SiO2 nanofibers are added, the stirring rate is adjusted to 2400r / min, and the stirring time is 60min to obtain a uniform suspension.

[0069] Repeat the above operation for 2 more times, then put all the 3 suspensions into a polytetrafluoroethylene mold (size 34cm*34cm*2cm), then put the mold into a directional freezing device with a unidirectional temperature gradient distribution, the bottom of the mold is in contact with the copper block in the directional freezing device, and the copper block plays a role of unidirectional freezing; directional freezing is performed for 90 minutes when the copper block temperature is -80°C. During the directional freezing process, the directional freezing device is covered with heat insulation cotton to isolate heat and ensure the unidirectional nature of temperature transfer to the greatest extent.

[0070] After being completely frozen, it was transferred to a freeze dryer and vacuum dried for 72 hours at a vacuum degree of 8.8 Pa and a water-filled cold trap temperature of -60°C. It was then transferred to a muffle furnace and heated to 800°C at a heating rate of 2°C / min in an air atmosphere, and kept warm for 120 minutes to obtain nanofiber aerogel.

[0071] Figure 3 This is a macroscopic morphology of the suspension in Example 2.

[0072] Figure 4 This is a macroscopic morphology of the product of Example 2.

[0073] Effect Example 1

[0074] In the process of preparing nanofiber aerogel, various shapes can be prepared by replacing different molds. In order to verify this property, the present invention prepared a variety of samples by only adjusting the shape of the polytetrafluoroethylene mold in Example 2. The actual picture is as follows Figure 5 shown.

[0075] Figure 5 This is a macroscopic morphology of the nanofiber aerogel prepared according to the method of Effect Example 1.

[0076] Depend on Figure 5 As shown, the product size is limited only by the size of the freeze dryer.

[0077] Example 3

[0078] Preparation of nanofiber aerogel:

[0079] In a 150mL beaker, add 72g of deionized water, 8g of silica sol (silicon dioxide concentration is 10wt%), and 0.4g of TiO2 particles, put it into an ultrasonic cell disruptor, and ultrasonically disperse it at a power of 120W for 5 minutes to obtain a uniform premixed solution. Put it into a water bath at room temperature, adjust the stirring rate to 600r / min, and gradually heat the water bath to 70°C. When the temperature of the premixed solution reaches 70°C, add 0.8g of gelatin powder, adjust the stirring rate to 1600r / min until the gelatin powder is completely dissolved in the premixed solution, then add 0.8g of SiO2 nanofibers, adjust the stirring rate to 1800r / min, and stir for 30min to obtain a uniform suspension.

[0080] The suspension is placed in a polytetrafluoroethylene mold, and then the mold is placed in a directional freezing device with a unidirectional temperature gradient distribution. The bottom of the mold is in contact with the copper block in the directional freezing device, and the copper block plays a role of unidirectional freezing; the directional freezing is carried out for 90 minutes when the temperature of the copper block is -80°C. During the directional freezing process, the directional freezing device is surrounded by heat insulation cotton to isolate heat and ensure the unidirectionality of temperature transfer to the greatest extent.

[0081] After being completely frozen, it was transferred to a freeze dryer and vacuum dried for 72 hours at a vacuum degree of 13.4Pa and a water-filled cold trap temperature of -60°C. It was then transferred to a muffle furnace and heated to 800°C at a heating rate of 2°C / min in an air atmosphere, and kept warm for 120 minutes to obtain nanofiber aerogel.

[0082] The measured density of the product of Example 3 is 34.9 mg / cm 3The compressive strength is 13.15KPa, the thermal conductivity is 0.0268W / (m·K) at room temperature, and the thermal conductivity is 0.0698W / (m·K) at 800°C. The product was cut into 50mm thickness, and its sound absorption coefficient at 800Hz was measured to be 0.87.

[0083] Figure 6 The figure is a high temperature resistance effect diagram of the product of Example 3 under an alcohol lamp.

[0084] Figure 7 This is a diagram showing the high temperature resistance of the product of Example 3 under a butane blowtorch.

[0085] Figure 6 and Figure 7 The high temperature stability of the nanofiber aerogel prepared in Example 3 under the heat source of an alcohol lamp and a butane burner is demonstrated, and it is expected to be used in extremely high temperature fields.

[0086] Example 4

[0087] Preparation of nanofiber aerogel:

[0088] In a 150mL beaker, add 72g of deionized water, 8g of silica sol (silicon dioxide concentration is 10wt%), and 0.4g of potassium hexatitanate whisker, put it into an ultrasonic cell disruptor, and ultrasonically disperse it at a power of 240W for 5min to obtain a uniform premixed solution, put it into a water bath at room temperature, adjust the stirring rate to 600r / min, and gradually heat the water bath to 85°C. When the temperature of the premixed solution reaches 85°C, add 0.8g of carrageenan powder, adjust the stirring rate to 1200r / min until the carrageenan powder is completely dissolved in the premixed solution, then add 0.8g of SiO2 nanofibers, adjust the stirring rate to 1800r / min, and stir for 30min to obtain a uniform suspension.

[0089] The suspension is placed in a polytetrafluoroethylene mold, and then the mold is placed in a directional freezing device with a unidirectional temperature gradient distribution. The bottom of the mold is in contact with the copper block in the directional freezing device, and the copper block plays a role of unidirectional freezing; the directional freezing is carried out for 90 minutes when the temperature of the copper block is -80°C. During the directional freezing process, the directional freezing device is surrounded by heat insulation cotton to isolate heat and ensure the unidirectionality of temperature transfer to the greatest extent.

[0090] After being completely frozen, it was transferred to a freeze dryer and vacuum dried for 72 hours at a vacuum degree of 14.9 Pa and a water-filled cold trap temperature of -60°C. It was then transferred to a muffle furnace and heated to 800°C at a heating rate of 2°C / min in an air atmosphere, and kept warm for 120 minutes to obtain nanofiber aerogel.

[0091] It was measured that the density of the product of Example 4 was 32.5 mg / cm3 The compressive strength is 10.61KPa, the thermal conductivity is 0.0257W / (m·K) at room temperature, and the thermal conductivity is 0.0682W / (m·K) at 800°C. The product was cut into 50mm thickness, and its sound absorption coefficient at 800Hz was measured to be 0.91.

[0092] Figure 8 This is the compression-rebound diagram of the product of Example 4 at room temperature.

[0093] Figure 8 It can be seen that the product of Example 4 can fully rebound under a strain of 30%, and can play a good buffering role when dealing with strong impact or instantaneous stress in actual application.

[0094] Example 5

[0095] Preparation of nanofiber aerogel:

[0096] In a 150mL beaker, add 72g deionized water, 8g silica sol (concentration of silicon dioxide is 10wt%), 0.4gB4C particle, put into ultrasonic cell crusher, ultrasonic dispersion 5min under power 150W, obtain uniform premix, put into the water-bath of normal temperature, regulating stir speed (S.S.) is 600r / min, progressively water-bath is warming up to 95 ℃, add 0.8g konjac glucomannan powder when the premix temperature reaches 95 ℃, regulating stir speed (S.S.) is 1200r / min until konjac glucomannan powder is dissolved fully in the premix, then add 0.8g SiO2 nanofiber, regulating stir speed (S.S.) is 1800r / min, and churning time is 30min, obtains uniform suspension.

[0097] The suspension is placed in a polytetrafluoroethylene mold, and then the mold is placed in a directional freezing device with a unidirectional temperature gradient distribution. The bottom of the mold is in contact with the copper block in the directional freezing device, and the copper block plays a role of unidirectional freezing; the directional freezing is carried out for 90 minutes when the temperature of the copper block is -80°C. During the directional freezing process, the directional freezing device is surrounded by heat insulation cotton to isolate heat and ensure the unidirectionality of temperature transfer to the greatest extent.

[0098] After being completely frozen, it was transferred to a freeze dryer and vacuum dried for 72 hours at a vacuum degree of 18.8Pa and a water-filled cold trap temperature of -60°C. It was then transferred to a muffle furnace and heated to 800°C at a heating rate of 2°C / min in an air atmosphere, and kept warm for 120 minutes to obtain nanofiber aerogel.

[0099] The measured density of the product of Example 5 is 34.1 mg / cm 3The compressive strength is 12.73KPa, the thermal conductivity is 0.0274W / (m·K) at room temperature, and the thermal conductivity is 0.0712W / (m·K) at 800°C. The product was cut into 50mm thickness, and its sound absorption coefficient at 800Hz was measured to be 0.84.

[0100] Example 6

[0101] Preparation of nanofiber aerogel:

[0102] In a 150mL beaker, add 72g of deionized water, 8g of silica sol (silicon dioxide concentration is 10wt%), and 0.4g of SiC whisker, put it into an ultrasonic cell disruptor, and ultrasonically disperse it at a power of 240W for 5min to obtain a uniform premixed solution, put it into a water bath at room temperature, adjust the stirring rate to 600r / min, and gradually heat the water bath to 73°C. When the temperature of the premixed solution reaches 73°C, add 0.8g of gellan gum powder, adjust the stirring rate to 1200r / min until the gellan gum powder is completely dissolved in the premixed solution, then add 0.8g of SiO2 nanofibers, adjust the stirring rate to 1800r / min, and stir for 30min to obtain a uniform suspension.

[0103] The suspension is placed in a polytetrafluoroethylene mold, and then the mold is placed in a directional freezing device with a unidirectional temperature gradient distribution. The bottom of the mold is in contact with the copper block in the directional freezing device, and the copper block plays a role of unidirectional freezing; the directional freezing is carried out for 90 minutes when the temperature of the copper block is -80°C. During the directional freezing process, the directional freezing device is surrounded by heat insulation cotton to isolate heat and ensure the unidirectionality of temperature transfer to the greatest extent.

[0104] After being completely frozen, it was transferred to a freeze dryer and vacuum dried for 72 hours at a vacuum degree of 16.6Pa and a water-filled cold trap temperature of -60°C. It was then transferred to a muffle furnace and heated to 800°C at a heating rate of 2°C / min in an air atmosphere, and kept warm for 120 minutes to obtain nanofiber aerogel.

[0105] It was measured that the density of the product of Example 6 was 35.5 mg / cm 3 The compressive strength is 13.89KPa, the thermal conductivity is 0.0249W / (m·K) at room temperature, and the thermal conductivity is 0.0667W / (m·K) at 800°C. The product was cut into 50mm thickness, and its sound absorption coefficient at 800Hz was measured to be 0.96.

[0106] Examples 1-6 mainly explore the effects of different infrared sunscreens and hydrophilic colloids on the preparation process and material properties, and the following comparative examples 1-8 mainly explore the effects of the amount of reactants added on the material properties.

[0107] Comparative Example 1

[0108] The only difference from Example 1 is that the amount of deionized water added is changed to 76 g, and the amount of silica sol added is changed to 4 g.

[0109] It was measured that the density of the product of comparative example 1 (denoted as SWSNA0.5) was 35.2 mg / cm 3 , the compression strength is 9.19KPa.

[0110] Comparative Example 2

[0111] The only difference from Example 1 is that the amount of deionized water added is changed to 68 g, and the amount of silica sol added is changed to 12 g.

[0112] It was measured that the density of the product of comparative example 2 (denoted as SWSNA1.5) was 35.4 mg / cm 3 , the compression strength is 13.73KPa.

[0113] Comparative Example 3

[0114] The only difference from Example 1 is that the amount of deionized water added is changed to 64 g, and the amount of silica sol added is changed to 16 g.

[0115] It was measured that the density of the product of comparative example 3 (denoted as SWSNA2.0) was 40.3 mg / cm 3 , the compression strength is 18.50KPa.

[0116] Comparative Example 4

[0117] The only difference from Example 1 is that the addition of SiC whiskers is omitted.

[0118] It was measured that the density of the product of Comparative Example 4 (denoted as SWOSNA) was 26.7 mg / cm 3 The compressive strength is 7.56KPa, the thermal conductivity is 0.0208W / (m·K) at room temperature, and the thermal conductivity is 0.0787W / (m·K) at 800°C. The product was cut into 50mm thickness, and its sound absorption coefficient at 800Hz was measured to be 0.72.

[0119] Comparative Example 5

[0120] The only difference from Example 1 is that the added amount of SiC whiskers is changed to 0.08 g.

[0121] It was found that the density of the product of comparative example 5 (denoted as SW0.1SNA) was 29.8 mg / cm 3The compressive strength is 8.8KPa, the thermal conductivity is 0.0217W / (m·K) at room temperature, and the thermal conductivity is 0.0684W / (m·K) at 800°C. The product was cut into 50mm thickness, and its sound absorption coefficient at 800Hz was measured to be 0.84.

[0122] Fig. 9 This is a diagram showing the pressure-bearing effect of the product of comparative example 5 when placed above the pistil in a natural environment.

[0123] from Fig. 9 It can be seen that when this product is placed on the pistil, the pistil has almost no deformation, which can greatly reduce the coating weight of the material during actual application.

[0124] Comparative Example 6

[0125] The only difference from Example 1 is that the added amount of SiC whiskers is changed to 0.32 g.

[0126] It was measured that the density of the product of Comparative Example 6 (denoted as SW0.4SNA) was 32.3 mg / cm 3 The compressive strength is 10.68KPa, the thermal conductivity is 0.0236W / (m·K) at room temperature, and the thermal conductivity is 0.0668W / (m·K) at 800°C. The product was cut into 50mm thickness, and its sound absorption coefficient at 800Hz was measured to be 0.91.

[0127] Fig.10 These are the actual pictures of the in-situ compression rebound of the product of Comparative Example 6 at -196°C and 600°C respectively.

[0128] from Fig.10 It can be seen that the prepared material has temperature-invariant superelasticity. When encountering some extreme conditions such as thermal shock or low-temperature freezing, it can remain in its original state and can be used for a long time.

[0129] Comparative Example 7

[0130] The only difference from Example 1 is that the added amount of SiC whiskers is changed to 0.56 g.

[0131] It was measured that the density of the product of comparative example 7 (denoted as SW0.7SNA) was 36.1 mg / cm 3 The compressive strength is 15.55KPa, the thermal conductivity is 0.0248W / (m·K) at room temperature, and the thermal conductivity is 0.0633W / (m·K) at 800°C. The product was cut into 50mm thickness, and its sound absorption coefficient at 800Hz was measured to be 0.96.

[0132] Comparative Example 8

[0133] The only difference from Example 1 is that the added amount of SiC whiskers is changed to 0.8 g.

[0134] It was measured that the density of the product of Comparative Example 8 (denoted as SW1.0SNA) was 39.8 mg / cm 3 The compressive strength is 18.82KPa, the thermal conductivity is 0.0259W / (m·K) at room temperature, and the thermal conductivity is 0.0643W / (m·K) at 800°C. The product was cut into 50mm thickness, and its sound absorption coefficient at 800Hz was measured to be 0.99.

[0135] Fig.11 The figure is a comparison chart of the compression-rebound curves of the products of Example 1 and Comparative Examples 1-3 at 60%.

[0136] Fig.12 It is a comparison chart of the compression-rebound curves of the product of Example 1 at 20%, 40%, and 60%.

[0137] Fig.13 It is a comparison chart of the compression-rebound curves of the products of Comparative Examples 4-8 at 60%.

[0138] from Fig.11 , 12 , 13 It can be found that it has good compression rebound properties and is a good choice for coating materials.

[0139] Fig.14 This is a temperature difference diagram of the hot and cold surfaces of the product of Comparative Example 8 under a butane spray gun.

[0140] It can be seen from the figure that when the hot surface temperature is stabilized at 1050°C, the cold surface temperature is stabilized at 171°C. The extremely large temperature difference of 879°C indicates that the prepared material has excellent high-temperature thermal insulation properties and is a good choice for extreme thermal protection materials.

[0141] Fig.15 This is a comparison chart of the sound absorption coefficient of the product of Comparative Example 8 when cut to a thickness of 30 mm and that of commercial glass fiber felt.

[0142] Depend on Fig.15 It can be found that its sound absorption coefficient is greater than that of commercial glass fiber felt between 500 and 2000 Hz, which further proves that it has excellent sound absorption performance.

[0143] Effect Example 2

[0144] In order to further compare the performance of the prepared nanofiber aerogel with that of commercial materials, Fig.16 A direct comparison of the thermal insulation and sound absorption properties of the nanofiber aerogel prepared in Comparative Example 8 and other common materials is shown.

[0145] Fig.16The figure is a direct comparison of the thermal insulation and sound absorption performance of the product of comparative example 8 and other common materials. Among them, (a) is a physical picture of nanofiber aerogel, glass fiber felt, ceramic fiber felt, and carbon felt, (b)-(d) are temperature imaging pictures of each material after heating for 30s, 300s, and 600s, respectively, (e) is a physical picture of the device for measuring the sound absorption coefficient in a small reverberation chamber made by the present invention, and (f)-(h) are sound intensity cloud pictures when no sound absorbing material is placed, glass fiber felt is placed, and nanofiber aerogel is placed, respectively.

[0146] Among them, (a) is a physical picture of the nanofiber aerogel (SWSNAs) of comparative example 8 and glass fiber mat (Glass fibermat), ceramic fiber mat (Ceramic fiber mat), and carbon mat (Carbon mat); (b)-(d) are temperature imaging pictures of the nanofiber aerogel, glass fiber mat, ceramic fiber mat, and carbon mat heated to 400°C on a flat heater after 30s, 300s, and 600s, respectively. It can be seen from the pictures taken with an infrared camera that after 600s, the surface temperature of the nanofiber aerogel prepared by the present invention is the lowest, which is 95.1°C, and the surface temperatures of the other three materials are all over 150°C. (e) is a physical picture of the device for measuring the sound absorption coefficient of the self-made small reverberation chamber of the present invention (including a small reverberation box and a sound intensity probe), (f)-(h) are sound intensity cloud maps when no sound absorbing material is placed, glass fiber felt is placed, and nanofiber aerogel is placed, respectively. The sound intensity cloud map of the material surface is generated by testing with the sound intensity probe; it can be clearly seen that the sound absorption performance of the nanofiber aerogel is significantly better than that of the commercial glass fiber felt. The noise of 80dB is only 65dB after passing through the nanofiber aerogel, while it is still above 70dB after passing through the commercial glass fiber felt.

[0147] Fig.17 The morphology comparison diagram of the product of Example 1 of the present invention and the filamentous bristle structure on the surface of the organ of the white blind shrimp. Among them, (a) is a macroscopic morphology diagram of the white blind shrimp, (b) and (c) are respectively microscopic morphology diagrams of the filamentous bristle structure on the surface of the organ of the white blind shrimp at different magnifications, (d) is an axial microscopic morphology diagram of the product of Example 1, and (e)-(f) are respectively radial microscopic morphology diagrams of the product of Example 1 at different magnifications.

[0148] Table 1 Effect of different SiC whisker addition amounts on material properties

[0149]

[0150] Table 1 shows the effect of different SiC whisker addition amounts on material properties. It can be seen that with the increase of the infrared sunscreen content, the density increases, and its compressive strength increases. At the same time, due to the increase in density, the thermal conductivity at room temperature also increases, but because the infrared sunscreen whiskers reduce the infrared transmittance, the thermal conductivity of Comparative Examples 5-8 at 800°C is significantly reduced relative to Comparative Example 4, and can reach a minimum of 0.0633W / (m·K). Further increase in SiC whiskers will affect the overall solid phase content of the sample, and may increase the thermal conductivity of the material. With the increase of SiC whiskers, the SiC whiskers attached to the wall of the directional holes of the material also continue to increase, the roughness of its surface continues to increase, the dissipation of sound waves is gradually enhanced, and the sound absorption performance of the material is gradually improved.

[0151] Table 2 Effects of different infrared sunscreen agents and hydrophilic colloids on material properties

[0152]

[0153] Table 2 shows the effects of different infrared sunscreens and hydrophilic colloids on material properties. Since the final products differ only in the type of infrared sunscreen, their compression strengths are similar. SiC whiskers have the lowest thermal conductivity due to the presence of stacking faults, which reduces solid-phase thermal conduction, and B4C particles have the highest thermal conductivity. Examples 1, 4, and 6 are whisker-type infrared sunscreens, whose higher aspect ratio increases the frictional specific surface area between them and sound waves, and their sound absorption performance is significantly better than that of particle-type infrared sunscreens (Examples 3 and 5).

[0154] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a bionic nanofiber aerogel with integrated thermal insulation, noise reduction and fire prevention functions, characterized in that: The following steps are involved: The silica sol and water are mixed to obtain a premixed solution, and then a hydrophilic colloid and SiO2 nanofibers are added and mixed evenly to obtain a suspension; Directionally freezing the suspension, vacuum drying it, and sintering it to obtain the bionic nanofiber aerogel with integrated thermal insulation, noise reduction, and fireproof functions; The process of mixing the silica sol and water also includes the step of adding an infrared sunscreen; the mass ratio of the silica sol, the infrared sunscreen, the water, the hydrophilic colloid and the SiO2 nanofiber is 1-4:0.2:16-19:0.2:0.2; The directional freezing is as follows: placing the suspension into a mold, and then placing the mold into a directional freezing device with a unidirectional temperature gradient distribution for directional freezing; The bottom of the mold is in contact with the copper block in the directional freezing device with unidirectional temperature gradient distribution, and the copper block plays a role of unidirectional freezing. The temperature of the copper block is -70°C to -196°C, and the directional freezing time is 30 to 120 minutes. The internal environment temperature of the dryer during vacuum drying is -50°C to 50°C, the water supply cold trap temperature is -70°C to -45°C, the drying time is 72h, and the vacuum degree is 5 to 30Pa; the sintering is performed by heating the temperature to 800°C at a heating rate of 2°C / min and then keeping the temperature for 120min, and the sintering atmosphere is air atmosphere; The hydrophilic colloid is one or more of agarose, pectin, gelatin, carrageenan, gellan gum and konjac gum.

2. The preparation method according to claim 1, characterized in that: The concentration of silicon dioxide in the silica sol is 10 wt %.

3. The preparation method according to claim 1, characterized in that: The infrared sunscreen is one or more of SiC whiskers, TiO2 particles, potassium hexatitanate whiskers and B4C particles; the diameter of the SiC whiskers and potassium hexatitanate whiskers is ≤1 μm, and the aspect ratio is ≤20; the particle size of the TiO2 particles and B4C particles is ≤1 μm.

4. The preparation method according to claim 1, characterized in that: The preparation method of the SiO2 nanofiber is: First, the SiO2 nanofiber membrane is cut into small pieces, and pre-cut using a wall breaking machine for 3 minutes to obtain a SiO2 nanofiber suspension without obvious SiO2 nanofiber membrane pieces, and then homogenized and cut at a speed of 3000-20000r / min for 5-20min to obtain a homogenous liquid, which is then dried at 120°C for 24h to obtain the SiO2 nanofibers.

5. A bionic nanofiber aerogel with integrated insulation, noise reduction and fire prevention functions obtained according to the preparation method according to any one of claims 1 to 4.

6. The bionic nanofiber aerogel with integrated heat insulation, noise reduction and fire prevention functions according to claim 5 is characterized in that: The density of the aerogel is 5 to 50 mg / cm 3 The thermal conductivity at room temperature is 0.0208~0.0274W / (m·K), and the high temperature thermal conductivity at 800℃ is 0.0633~0.0787W / (m·K).

Citation Information

Patent Citations

  • Preparation method of light heat-insulating mullite nanofiber aerogel

    CN110078425A

  • Preparation method of intense-radiation-resistant block material stable having low density and stability at superhigh temperature

    CN104291773A

  • Preparation method of ceramic aerogel material with high strength and low thermal conductivity

    CN115849949A